TGF-β1 as possible link between loss of bone mineral density and chronic inflammation - Ehnert, Sabrina; Baur, Johannes; Schmitt, Andreas; Neumaier, Markus; Lucke, Martin; Dooley, Steven; Vester, Helen; Wildemann, Britt; Stöckle, Ulrich; Nussler, Andreas K. (PLOS ONE, 2010)
Background The TGF family plays a key role in bone homeostasis. Systemic or topic application of proteins of this family apparently positively affects bone healing in vivo. However, patients with chronic inflammation, having increased TGF-β1 serum-levels, often show reduced bone mineral content and disturbed bone healing. Therefore, we wanted to identify intracellular mechanisms induced by chronic presence of TGF-β1 and their possible role in bone homeostasis in primary human osteoblasts. Methodology/Principal Findings Osteoblasts were isolated from femur heads of patients undergoing total hip replacement. Adenoviral reporter assays showed that in primary human osteoblasts TGF-β1 mediates its signal via Smad2/3 and not Smad1/5/8. It induces proliferation as an intermediate response but decreases AP-activity and inorganic matrix production as a late response. In addition, expression levels of osteoblastic markers were strongly regulated (AP↓; Osteocalcin↓; Osteopontin↑; MGP↓; BMP 2↓; BSP2↓; OSF2↓; Osteoprotegerin↓; RANKL↑) towards an osteoclast recruiting phenotype. All effects were blocked by inhibition of Smad2/3 signaling with the Alk5-Inhibitor (SB431542). Interestingly, a rescue experiment showed that reduced AP-activities did not recover to base line levels, even 8 days after stopping the TGF-β1 application. Conclusions/Significance In spite of the initial positive effects on cell proliferation, it is questionable if continuous Smad2/3 phosphorylation is beneficial for bone healing, because decreased AP-activity and BMP2 levels indicate a loss of function of the osteoblasts. Thus, inhibition of Smad2/3 phosphorylation might positively influence functional activity of osteoblasts in patients with chronically elevated TGF-β1 levels and thus, could lead to an improved bone healing in vivo.
Gesehen am 22.05.2023
Im Titel ist die Ziffer 1 bei TGF-β1 tiefgestellt